Pengaruh Persepsi Keragaman Tim dan Budaya Inovasi Persepsian pada Perilaku Kerja Inovatif Karyawan PT. Bank Mandiri, TBK, Area Sleman - , Nedo Dana Kesatrya; , Prof. Dr. Djamaluddin Ancok, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This reseach was aimed to test the influence of perception of team diversity and perceived innovation culture on innovative work behavior of employeeâs PT. Bank Mandiri Sleman area. This study assumed perception of team diversity and perceived innovation culture positive influence and significant on employee innovative work behavior. So the higher of perception of team diversity and perceived innovation culture, the better the employee innovative work behavior. The data for this study are using a questionnaire distributed to all employees of PT. Bank Mandiri Sleman area 140 people. The questionnaires were filled and returned to the researchers by 99 people. Data that has been collected analyzed using descriptive analysis and inferential statistical multiple linear regression, F test and t test. The results of the descriptive analysis shows the components of perception and cultural diversity of team innovation persepsian well with high marks. While the results of inferential statistical analysis indicates that there is a positive and significant perception of cultural diversity and team innovation persepsian simultaneously on innovative work behavior with significance value 0.000 <0.05. The value of correlation 0.475, coefficient of determination 0.225 and the regression equation Y = 26.662 + 0.178 + 0.139 Xa Xb. For the first hypothesis significance value 0.237 > 0.05 so it is not supported, while for the second hypothesis significance value 0.001 <0.05 so supported.